Difficult risks and capital models: a report from the Extreme Events Working Party ‐ Abstract of the Edinburgh Discussion. (22nd May 2014) - Sharp, Alexander
<x content-type="archive" xml:space="preserve">Abstract</x> This abstract relates to the following paper: <mixed-citation id="refa1" publication-type="journal"><string-name><given-names>R.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Frankland</surname></string-name><string-name><given-names>S.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Eshun</surname></string-name><string-name><given-names>L.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Hewitt</surname></string-name><string-name><given-names>P.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Jakhria</surname></string-name><string-name><given-names>S.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Jarvis</surname></string-name><string-name><given-names>A.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Rowe</surname></string-name><string-name><given-names>A.D.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Smith</surname></string-name><string-name><given-names>A.C.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Sharp</surname></string-name><string-name><given-names>J.</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Sharpe</surname></string-name> and <string-name><given-names>T</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Wilkins</surname></string-name> Difficult risks and capital models: a report from the Extreme Events Working Party . <source>British Actuarial Journal</source>, doi: <pub-id pub-id-type="doi">10.1017/S1357321713000524</pub-id></mixed-citation>